Longitudinal analysis of myelin oligodendrocyte glycoprotein antibodies in CNS inflammatory diseases. - Hyun, JW; Woodhall, MR; Kim, SH; Jeong, IH; Kong, B; Kim, G; Kim, Y; Park, MS; Irani, SR; Waters, PJ; Kim, HJ (BMJ Publishing Group, 2017)
Background We evaluated the seroprevalence of myelin oligodendrocyte glycoprotein immunoglobulin G1 (MOG-IgG) and associated clinical features of patients from a large adult-dominant unselected cohort with mainly relapsing central nervous system (CNS) inflammatory diseases. We also investigate the clinical relevance of MOG-IgG through a longitudinal analysis of serological status over a 2-year follow-up period. Methods Serum samples from 505 patients with CNS inflammatory diseases at the National Cancer Center were analysed using cell-based assays for MOG-IgG and aquaporin-4 immunoglobulin G (AQP4-IgG). MOG-IgG serostatus was longitudinally assessed in seropositive patients with available serum samples and at least 2 years follow-up. Results Twenty-two of 505 (4.4%) patients with CNS inflammatory diseases were positive for MOGIgG. Patients with MOG-IgG had neuromyelitis optica spectrum disorder (NMOSD, n=10), idiopathic AQP4-IgGnegative myelitis (n=4), idiopathic AQP4-IgG-negative optic neuritis (n=4), other demyelinating syndromes (n=3) and multiple sclerosis (n=1). No relapses were seen in patients when they became MOG-IgG seronegative, whereas a persistent positive serological status was observed in patients with clinical relapses despite immunotherapy. Conclusions In a large adult-predominant unselected cohort of mainly relapsing CNS inflammatory diseases, we confirmed that NMOSD phenotype was most commonly observed in patients with MOG-IgG. A longitudinal analysis with 2-year follow-up suggested that persistence of MOG-IgG is associated with relapses.